Antenatal dietary patterns and depressive symptoms during pregnancy and early post‐partum. Issue 1 (3rd January 2016) - Baskin, Rachel; Hill, Briony; Jacka, Felice N; O'Neil, Adrienne; Skouteris, Helen
Abstract: Perinatal depression is a debilitating disorder experienced during pregnancy and/or the first year post‐partum. Recently, maternal dietary intake during pregnancy has emerged as a possible area of intervention for the prevention of mental disorders in women and their offspring. However, the relationship between antenatal diet quality and perinatal depressive symptoms remains poorly understood. The current study explored the predictive role of antenatal diet quality for antenatal and post‐natal depressive symptoms. Pregnant women ( n = 167) were recruited between February 2010 and December 2011. Women completed the Edinburgh Postnatal Depression Scale at time 1 [T1, mean weeks gestation = 16.70, standard deviation ( SD ) = 0.91], time 2 (T2, mean weeks gestation = 32.89, SD = 0.89) and time 3 (T3, mean weeks post‐partum = 13.51, SD = 1.97) and a food frequency questionnaire at T1 and T2. Diet quality was determined by extracting dietary patterns via principal components analysis. Two dietary patterns were identified: 'healthy' (including fruit, vegetables, fish and whole grains) and 'unhealthy' (including sweets, refined grains, high‐energy drinks and fast foods). Associations between dietary patterns and depressive symptoms were investigated by path analyses. While both 'healthy' and 'unhealthy' path models showed good fit, only one significant association consistent with study hypotheses was found, an 'unhealthy' diet was associated with increased depressive symptoms at 32 weeks gestation. Given that this association was cross‐sectional, it was not possible to make any firm conclusions about the predictive nature of either dietary patterns or depressive symptoms. Dietary intervention studies or larger prospective studies are therefore recommended.